Lung metastasis-targeted donut-shaped nanostructures shuttled by the margination effect for the PolyDox generation-mediated penetrative delivery into deep tumors. Issue 4 (29th January 2020) - Chiang, Min-Ren; Su, Yu-Lin; Chang, Chih-Yi; Chang, Chein-Wen; Hu, Shang-Hsiu
Abstract : A donut-shaped nanostructure effectively approaches the tumor and offers burst penetrative delivery of a large payload of drug to overcome tumor heterogeneity. Abstract : A donut-shaped nanostructure that can effectively approach lung metastasis and offer a burst penetrative delivery to overcome tumor heterogeneity has been proposed. The intravenously injected donut serves as a tumor-adhesion agent via the margination effect and hierarchical donut-shaped nanostructure, which drives nanoparticle-induced extracellular leakiness (nanoEL) both in vitro and in vivo . In an animal metastasis model, more than 72% of donuts localize to lung metastatic tumors instead of normal tissues. Upon the application of a high-frequency magnetic field (MF), a burst generation of polydox (pDox) particles from the carbon porous reservoirs of donuts enhances the retention in the deep tumor, facilitating penetrative delivery. Via pH-responsive hydrozone bonds, the penetrative pDox particles are cleaved into doxorubicin (Dox), yielding high intracellular concentrations of activated Dox at the tumor. The donut-shaped nanostructure loaded with pDox improved the survival rates in a mouse model of metastatic lung cancer and the activity of immune response.